Multi-Threaded Ant Colony Optimization with Asynchronous Communications for the Vehicle Routing Problem - Maria Lucka; Stanislav Piecka (Communications - Scientific letters of the University of Zilina, 2009)
In this paper we study behaviour of Ant Colony Optimization algorithm for solving the Vehicle Routing Problem implemented by POSIX Threads in parallel cluster environment. The algorithm is based on a fine-grained parallelism strategy which uses asynchronous communication for cooperation in finding solutions. Our aim is to analyze the effect of proposed method on speedup, execution and communication time with respect to the quality of solution.